Process model abstraction for rapid comprehension of complex business processes. Issue 103 (January 2022) - Tsagkani, Christina; Tsalgatidou, Aphrodite
Abstract: Business process management has been widely adopted by many organizations, ​ resulting in the accumulation of large collections of process models. The majority of these models are rather large and complex. Even though such models constitute a great source of knowledge, they cannot be easily understood by all process stakeholders. Process model abstraction techniques have been proven effective in generating easy to comprehend, high-level views on business process models; thus, such techniques change the way that detailed process models may be utilized within an organization. Although much attention has been given to abstract activities of process models, to the best of our knowledge, there are no research works that deliver abstract process model views, by considering as candidates for abstraction not only activities but also other process model elements. In this paper, we present an abstraction approach that simplifies existing process models by focusing not only on the abstraction of activities, but also on the abstraction of data, roles, messages and artifacts. The proposed approach exploits both model structure and element properties, while it is grounded on a set of abstraction rules. A prototype tool has been implemented as a proof of concept; this tool has been used for validating the proposed approach by automatically applying the suggested abstraction rules to different sets of real-world process models. A number of process stakeholders have also been involved in this validation. Thus, it is empirically proved that the presented work is an effective process model abstraction method that increases the usability of complex business process models, as it enables their rapid comprehension by process stakeholders. Highlights: Large and complex business process models cannot be easily comprehended and utilized. Professionals at managerial levels need simplified models for decision making purposes. Business process abstraction facilitates quick comprehension of large process models. Business process abstraction enhances process model their usability within an organization. A holistic approach that exploits both process model structure and element properties. The approach fosters abstraction and rapid comprehension of complex business processes.